2016
DOI: 10.1111/pedi.12469
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders during early adulthood in those with childhood onset type 1 diabetes: Rates and clinical risk factors from population-based follow-up

Abstract: Our findings highlight the need for access to mental health support services as part of routine patient care for young adults with T1D, and for better predictive tools to facilitate targeting at-risk patients with early intervention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 36 publications
9
65
1
6
Order By: Relevance
“…Cooper et al . 41 found that young people with Type 1 diabetes (average age of 9 years at baseline) had a 2.5 times increased hazard of developing incident anxiety over 26 years. Furthermore, Huang et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cooper et al . 41 found that young people with Type 1 diabetes (average age of 9 years at baseline) had a 2.5 times increased hazard of developing incident anxiety over 26 years. Furthermore, Huang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as anxiety disorder tends to occur in adolescence or early adulthood 44 the approach taken by Cooper et al . 41 following people up from a younger age may better allow us to make inferences on diabetes as a cause of incident anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esto hace que para un adolescente con DMT1 el tratamiento diario sea aún más difícil de controlar 31 . Existe una mayor incidencia de problemas psicosociales en comparación a la población general, que alcanza a 2,3 veces 32 . No es raro que muchos adolescentes, presentan sentimientos de ira, miedo, infelicidad o incluso crisis de angustia por la presencia de la DMT1 2 .…”
Section: Adolescencia Y Problemas Psicosocialesunclassified
“…Muchos de los pacientes con diabetes relatan que tienen preocupación por las reacciones y los problemas con la familia, amigos y compañeros que no son diabéticos 1 . En los jóvenes diabéticos se ha reportado que los trastornos psiquiátricos más frecuentes son la ansiedad, depresión y trastornos alimenticios 1,5,32 . En Chile, jóvenes con DMT1 presentaron altos niveles de estrés, debido a los serios y complejos desafíos psicológicos y conductas, los que pueden llevar a presentar sínto-mas depresivos, mala adherencia a la insulinoterapia y llegar así a un pobre control metabólico 31 .…”
Section: Adolescencia Y Problemas Psicosocialesunclassified